Forward head posture and neck disability: what is the effect on lung function? - Giada Annarumma; Alessandro Spinelli; Alessandro Serio; Tammaro Di Fraia; Carlo Maria Gallinoro; Lucrezia Caoduro; Domiziano Tarantino; Andrea Demeco; Erica Keeling; Stefano Palermi; Alessandro Biffi; Felice Sirico (Exploration of Medicine, 2023)
Aim: Forward head posture (FHP) is a very common pathological neck posture among people who frequently use multimedia devices, and it could be related to some musculoskeletal disorders. However, its role in influencing lung function and its relationship with neck disability are still debated in the literature. Therefore, the aim of the present study was to investigate the influence of FHP on respiratory function, and to explore a possible relationship between FHP and neck discomfort. Methods: A cross-sectional study was conducted on a sample of 83 subjects (35.7 ± 8.4 years aged), enrolled at the Ferrari corporate wellness program “Formula Benessere”. Craniovertebral angle (CVA) was measured with a digital goniometer to assess head posture: FHP was defined with a CVA < 50° in an upright position. Spirometry was conducted according to European Respiratory Society/American Thoracic Society (ERS/ATS) criteria. Finally, subjects enrolled were evaluated through a self-administered neck disability index (NDI) questionnaire. Results: Among the 60 participants with agreement about the CVA measurements, 45 had FHP (11 females and 34 males) with lower CVA values. No significant differences were found in spirometric parameters between subjects with FHP (n = 45) and subjects without FHP (n = 15). Furthermore, the two groups did not differ either in NDI scores (P = 0.148). Conclusions: There is no clear relationship between FHP and respiratory function indices. Moreover, no differences have been found in NDI values between subjects with FHP and subjects without FHP. Respiratory rehabilitation strategies should be focused on other parameters than FHP itself.